Psychedelics : the revolutionary drugs that could change your life--a guide from the expert - Nutt, David J., 1951-; Moss, Brigid (Hachette Go, 2024)
"We are on the cusp of a major revolution in psychiatric medicine and neuroscience. After fifty years of prohibition, criminalization and fear, science is finally showing us that psychedelics are not dangerous or harmful. Instead, when used according to tested, safe and ethical guidelines, they are our most powerful newest treatment of mental health conditions, from depression, PTSD, and OCD to disordered eating and even addiction and chronic pain. Professor David Nutt, one of the world's leading Neuropsychopharmacologists, has spent 15 years researching this field and it is his most significant body of work to date. In 2018, he co-founded the first academic psychedelic research center--underpinned by his mission to provide evidence-based information for people everywhere. It revived interest in the understanding and use of this drug in its many forms, including MDMA, ayahuasca, magic mushrooms, LSD and ketamine. The results of this have been nothing short of ground-breaking for the future categorization of drugs, but also for what we now know about brain mechanisms and our consciousness. At a time where there is an enormous amount of noise around the benefits of psychedelics, this book contains the knowledge you need to know about a drug that is about to go mainstream, free from the hot air, direct from the expert."--Amazon.com.